Policy Analysis of The Regent’s Decision on Stunting in Nganjuk Regency - Ditania Arya Dewi,; Lina Aprilia, (Journal of Transformative Governance and Social Justice, 2025)
Stunting remains a significant public health challenge in Indonesia, including Nganjuk Regency, where high prevalence rates persist despite national intervention programs. Stunting, characterized by chronic malnutrition, affects children's physical and cognitive development, leading to long-term socioeconomic consequences. Addressing this issue requires comprehensive, data-driven policies supported by cross-sectoral collaboration and sustainable interventions. This study aims to analyze the policy of the Regent of Nganjuk on accelerating the reduction of stunting rates in 2023. The research evaluates the effectiveness of local government strategies in implementing national stunting reduction programs and identifies key challenges and opportunities for improvement. A qualitative approach was employed using a literature review to examine policy implementation and provide strategic recommendations. The study analyzed existing policies, regulatory frameworks, and best practices from other regions to assess their applicability in Nganjuk Regency The findings indicate that a data-driven approach, involving multi-sectoral collaboration and extensive community education, has positively impacted the reduction of stunting rates. However, significant challenges persist, including limited health personnel, inadequate infrastructure, and uneven access to essential healthcare services. Addressing these challenges requires strengthening monitoring and evaluation mechanisms and leveraging public-private partnerships through Corporate Social Responsibility (CSR) programs to ensure sustainability. The study recommends the establishment of a Regional Regulation (Perda) as a strong legal foundation for long-term stunting management. The conclusion emphasizes the need for synergy between the government, community, and private sector to achieve Indonesia’s national stunting reduction target of 14% by 2024. Effective implementation of policies at the local level is crucial in ensuring a healthier future for children in Nganjuk Regency.